Penerapan Konsep Sosiologis Di Sekolah Dasar - Triyono; Purnamasari, Iin (CV. Supernova Office Stationary and Printing, 2024)
Background: This research aims to determine the application of sociological science in the elementary school environment. Method: The research method used in this research uses a literature study which looks at article sources from scientific journals which contain sociological concepts applied in elementary schools. Results and discussion: Sociological studies of education emphasize the social impact and consequences of education and view educational problems from the perspective of all social, cultural, political and economic contexts that influence society. Sociology of education views educational phenomena as part of the social structure of society. Conclusion: It is very important to apply sociological concepts to students' learning in elementary schools for character formation.